Spectroscopic characterization of Mn-Co-Ce mixed oxides, active catalysts for COPROX reaction - Gómez, Leticia Ester (2013)
Mn-Co-Ce mixed oxides are active and selective catalysts for the CO preferential oxidation (COPROX), which is a promising process for the purification of hydrogen streams. In this work, we report a careful spectroscopic characterization of the said system, with the aim of relating its physical chemistry properties to the catalytic behavior. In all the Co-Mn-Ce samples, we detected the formation of partially developed (Mn,Co)3O4 mixed spinels. The presence of these species, which can be reduced during the TPR experiments at an intermediate temperature range (300-600°C), was also suggested by XRD and LRS. XPS results show that in all cases the catalytic surface is enriched in Mn, while the opposite occurs for Co. As regards the catalytic activity, we observed that the best formulations were those containing intermediate Mn/Co ratios (1/4 and 1/1), which can be ascribed to the promoting effect of Mn in improving the redox properties of Co active sites and provoking an increase in surface area. The best catalyst, which has a Mn/Co ratio of 1/4, was very stable after 75 h of time-on-stream with CO2 included in the feed.